2010
DOI: 10.1007/s12206-010-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of aluminum particle combustion with emphasis on the oxide effects and variable transport properties

Abstract: A simplified analytical modeling of single aluminum particle combustion was conducted. Ignition and quasi-steady combustion (QSC) were separately formulated and integrated. Both the heat transfer from the hot ambient gas and the enthalpy of heterogeneous surface reaction (HSR) served to cause the particle ignition. Conservation equations were solved for QSC parameters in conjunction with conserved scalar formulation and Shvab-Zeldovich function. Limit temperature postulate was formulated by a sink term pertine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This was in agreement with our previous result that the three distinctive stages represented heating, melting and evaporation until ignition [6]. Yang et al [19] and Ermakov et al [20] have reported the three-stage phenomenon for micron-sized aluminum during ignition. Trunov et al [21] developed a simplified ignition model and assumed that ignition occurs when the particle temperature exceeds the alumina melting point.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This was in agreement with our previous result that the three distinctive stages represented heating, melting and evaporation until ignition [6]. Yang et al [19] and Ermakov et al [20] have reported the three-stage phenomenon for micron-sized aluminum during ignition. Trunov et al [21] developed a simplified ignition model and assumed that ignition occurs when the particle temperature exceeds the alumina melting point.…”
Section: Resultssupporting
confidence: 93%
“…The flame appeared as a weak yellow at 1.909 ms, and there was a bright yellow flame at the lower left corner of the particle (Figure 10c). This showed quasi-steady-state combustion [19]. At 2.546 ms, the aluminum particle was completely covered by a yellow flame owing to a heterogeneous oxidation reaction at the surface.…”
Section: Resultsmentioning
confidence: 91%
“…Once the metal core is melted away into the liquid (a = 1), the particle temperature rises again. The rate of change of liquid mass fraction and overall liquid mass in the droplet can be expressed as [27,28]:…”
Section: Ignition Model Of Single Micron-sized Aluminummentioning
confidence: 99%
“…The ignition of aluminum may be initiated after the cracking of oxide film, but the removal of the oxide film concurrent with the oxide melting would be more probable cause for the particle ignition [27]. At the high heating rate (10 6 -10 8 K s À1 ), the oxide film will crack due to a large thermal stress at the interface between aluminum and the oxide film in stages I and II.…”
Section: Ignition Model Of Single Micron-sized Aluminummentioning
confidence: 99%
“…The three-staged ignition phenomenon was reported only for micron-sized aluminum [24,25], but it has never been experimentally demonstrated for nano aluminum at such high heating rates of the magnitude of 10 4 K/s. Ermakov et al [26] demonstrated that during ignition a horizontal melting length of micron-sized Al particle was visible.…”
Section: Ignition Stage Of Al Nanoparticlesmentioning
confidence: 99%